APLICACION DEL ANALISIS DIGITAL DE IMAGENES AL ESTUDIO DE LA CALIDAD DEL CORCHO - Molinas, M; Campos, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Digital Image Processing and Analysis (lA) es a computerized technique that permits to measure defined regions of interest of an image. For Al, digital images of the specimens are examined with appropiate software programs. In the present study an lA program for the quuantitative anatomy of cork has been developed. For this purpose IMAGE 1.41 VDM software for Macinstosh and Statview statistic software have been selected. Specimens from different cork populatins have been compared. The following cork parmeters: thickness, cork-rings and prososity have been measured in transverse and tangential sections. The results are analysed comparatively on each population and between populations.
Keywords: Cork quality; image analysis; morphometry; Quantitative anatomy; Quercus suber L.